Analysis of catabolic products of L-arginine; L-ornithine and L-citrulline and the residual L-arginine using the HPLC and LC-MS - Saranya Prashath (PLoS ONE, 2026)
L-arginine, a semi-essential amino acid, is metabolised in the cell to generate nitric oxide (NO) and L-citrulline via the enzyme nitric oxide synthase (NOS) or urea and L-ornithine via arginase activity. L-citrulline and L-ornithine are the products of L-arginine degradation. Mouse liver epithelial (BNL CL2) and mouse embryonic fibroblast (3T3 L1) insulin-sensitive cell lines were used as model systems and cultured with 0, 400 or 800 µM L-Arg. This study focuses on the analysis of the residual concentrations of amino acids (L-Arg, L-Cit and L-Orn) in cell culture medium samples using high performance liquid chromatography that involves precolumn derivatization with o-phthaldialdehyde. In BNL CL2 cells, most of the culture supernatant has increased amount of L-Arg in comparison to the control complete DMEM addition. L-ornithine levels showed an overall increase over time, with higher concentrations observed at 72 h compared with 24 h across all samples. In 3T3 L1 cells, residual L-Arg concentration decreased in most of the cell supernatant in comparison to the control at 72 h. Noticeably, L-Arg at 0 µM and the control complete DMEM had highest amount of L-Orn among all samples. Interestingly, L-Cit was very much high in culture medium of both untreated BNL CL2 (85.96 µM) and 3T3 L1 (37.49 µM) cells at T = 0 compared to the control. Collectively, the results show that excess L-Arg is sensed by the cell which then regulates the residual amount of amino acids concentration. The spectroscopy technique used here is highly sensitive, specific and accurate, can be readily automated and serves as a valuable tool for investigating the modulation of the arginine-nitric oxide pathway.